A non-selective cation conductance in frog muscle membrane blocked by micromolar external calcium ions. - Almers, W (1984)
Membrane currents were recorded from voltage-clamped, EGTA-loaded muscle fibres under conditions where currents through ordinary Na+, K+ and Cl- channels were prevented by drugs or by absence of permeant ions (K+, and Cl-). At 10 mM-external [Ca2+], substitution of Na+ for the large and presumably impermeant organic cations tetramethyl- (TMA+) or tetraethylammonium (TEA+) failed to increase peak inward current. Hence the Ca2+ channel was not significantly permeable to Na+ under these conditions. When external [Ca2+] was reduced to levels below 1 microM in the presence of external Na+, step depolarizations to negative potentials produced tetrodotoxin-resistant inward currents. At -20 mV, they rose to a peak of 30-200 microA/cm2 within 150 ms and declined thereafter. Ca2+ and several other divalent cations reversibly blocked this inward current. The sequence of blocking potencies was Ca2+ greater than Sr2+ greater than or equal to Co2+ greater than Mn2+ congruent to Cd2+ greater than Ni2+ congruent to Mg2+. Large inward currents may be carried by Li+, Na+, K+, Rb+ and Cs+ but not by TMA+ and TEA+. The effect of external Ca2+ ([Ca2+]o) was explored over a 10(8)-fold range in concentrations. Na+ was present at a fixed concentration. When [Ca2+]o was gradually increased from 10(-10) to 10(-2) M, inward current first diminished 10-fold, reached a minimum at [Ca2+]o = 60 microM and then increased again as [Ca2+]o was increased further and Ca2+ itself became a current carrier. Block of inward current at [Ca2+]o less than 10(-5) M could be described by binding of a single Ca2+ to a site, with a dissociation constant of the order of 0.7 microM at -20 mV.